Spatial and temporal organization of replicating Escherichia coli chromosomes. - Lau, I; Filipe, SR; Søballe, B; Økstad, O; Barre, F; Sherratt, D (2003)
The positions of DNA regions close to the chromosome replication origin and terminus in growing cells of Escherichia coli have been visualized simultaneously, using new widely applicable reagents. Furthermore, the positions of these regions with respect to a replication factory-associated protein have been analysed. Time-lapse analysis has allowed the fate of origins, termini and the FtsZ ring to be followed in a lineage-specific manner during the formation of microcolonies. These experiments reveal new aspects of the E. coli cell cycle and demonstrate that the replication terminus region is frequently located asymmetrically, on the new pole side of mid-cell. This asymmetry could provide a mechanism by which the chromosome segregation protein FtsK, located at the division septum, can act directionally to ensure that the septal region is free of DNA before the completion of cell division.